Modeling, Simulation, and Fabrication of a Fully Integrated, Acid‐stable, Scalable Solar‐Driven Water‐Splitting System. Issue 3 (7th January 2015) - Walczak, Karl; Chen, Yikai; Karp, Christoph; Beeman, Jeffrey W.; Shaner, Matthew; Spurgeon, Joshua; Sharp, Ian D.; Amashukeli, Xenia; West, William; Jin, Jian; Lewis, Nathan S.; Xiang, Chengxiang
Abstract A fully integrated solar‐driven water‐splitting system comprised of WO3/FTO/p+n Si as the photoanode, Pt/TiO2/Ti/n+p Si as the photocathode, and Nafion as the membrane separator, was simulated, assembled, operated in 1.0 M HClO4, and evaluated for performance and safety characteristics under dual side illumination. A multi‐physics model that accounted for the performance of the photoabsorbers and electrocatalysts, ion transport in the solution electrolyte, and gaseous product crossover was first used to define the optimal geometric design space for the system. The photoelectrodes and the membrane separators were then interconnected in a louvered design system configuration, for which the light‐absorbing area and the solution‐transport pathways were simultaneously optimized. The performance of the photocathode and the photoanode were separately evaluated in a traditional three‐electrode photoelectrochemical cell configuration. The photocathode and photoanode were then assembled back‐to‐back in a tandem configuration to provide sufficient photovoltage to sustain solar‐driven unassisted water‐splitting. The current–voltage characteristics of the photoelectrodes showed that the low photocurrent density of the photoanode limited the overall solar‐to‐hydrogen (STH) conversion efficiency due to the large band gap of WO3. A hydrogen‐production rate of 0.17 mL hr−1 and a STH conversion efficiency of 0.24 % was observed in a full cell configuration for >20 h with minimal product crossover in the fully operational, intrinsically safe, solar‐driven water‐splitting system. The solar‐to‐hydrogen conversion efficiency, ηSTH, calculated using the multiphysics numerical simulation was in excellent agreement with the experimental behavior of the system. The value of ηSTH was entirely limited by the performance of the photoelectrochemical assemblies employed in this study. The louvered design provides a robust platform for implementation of various types of photoelectrochemical assemblies, and can provide an approach to significantly higher solar conversion efficiencies as new and improved materials become available.